2007
DOI: 10.1111/j.1540-8159.2007.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Optimal VV Delay by an IEGM‐Based Method in Cardiac Resynchronization Therapy

Abstract: Determination of the optimal interventricular (VV) delay in cardiac resynchronization therapy currently relies on costly, time-consuming echocardiographic (ECHO) methods. This study evaluated the performance of a new intracardiac electrogram (IEGM)-based VV method compared to the aortic velocity time integral (AVTI) method of VV delay optimization. The study included two patient groups. Eleven patients enrolled by a single center in the Rhythm II ICD trial underwent prospective comparisons of the AVTI at the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 2 publications
(4 reference statements)
2
20
0
Order By: Relevance
“…A new validated tool (QuickOpt(tm), St. Jude Medical, Sylmar, CA, USA) based on intracardiac electrograms (IEGM) has been recently proposed to identify the individual optimal AV/PV and VV delays during device follow‐up 7,8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new validated tool (QuickOpt(tm), St. Jude Medical, Sylmar, CA, USA) based on intracardiac electrograms (IEGM) has been recently proposed to identify the individual optimal AV/PV and VV delays during device follow‐up 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…This device‐based optimization system was previously validated against aortic velocity time integral (VTI) measurements, with a >96% correlation coefficient for AV, PV, and VV delays 8 …”
Section: Introductionmentioning
confidence: 99%
“…The IEGM-CRT clinical study in over fifty subjects [1] demonstrated that the echo-Doppler derived aortic velocity integral (AVTI) values at the QuickOptpredicted AV, PV, and VV delays were linearly correlated with maximum AVTI, with Concordance Correlation Co-efficients (CCC) of 97.5%, 96.1% and 96.6% respectively. A retrospective analysis of data from SJM's RHYTHM study, where the VV intervals were optimized in sixty-one patients [2] also showed strong Concordance Correlation Co-efficient (CCC) =99%. Additional analysis of VV delays [3] was done retrospectively in the combined RHYTHM VV and IEGM-CRT patient cohorts.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, automated programmer algorithms based on intracardiac electrograms (IEGM) have been developed to expedite this process and is currently available in some CRT devices. Two small studies showed that the IEGM method correlated closely with A-V and V-V optimization determined by Doppler measured aortic valve VTI [49,50]. The IEGM method also was found to result in a higher degree of LV resynchronization and greater improvement in LV ejection fraction based on real-time three-dimensional echocardiographic assessment [28].…”
Section: Effects Of the Atrioventricular Interval On Hemodynamicsmentioning
confidence: 94%